2018
DOI: 10.1055/a-0585-0145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concomitant Administration of a Dipeptidyl Peptidase-4 Inhibitor in Japanese Patients with Type 2 Diabetes Showing Relatively Good Glycemic Control Under Treatment with a Sodium Glucose Co-Transporter 2 Inhibitor

Abstract: We conducted this study to determine whether additional administration of a dipeptidyl peptidase-4 (DPP-4) inhibitor might provide further improvement of the glycemic control in Japanese type 2 diabetes patients showing relatively good glycemic control under treatment with a sodium glucose co-transporter 2 (SGLT2) inhibitor. Five SGLT2 inhibitor (luseogliflozin, dapagliflozin, tofogliflozin, empagliflozin and canagliflozin) preparations and five DPP-4 inhibitor (sitagliptin, vildagliptin, alogliptin, anaglipti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
8
0
4
Order By: Relevance
“…Previous studies have examined the effects of various SGLT2 inhibitors on patients with T2DM and NAFLD [ 18 , 43 , 49 52 ]. They showed improvement in at least one liver enzyme level [ 31 , 43 , 49 , 50 , 52 ] and in hepatic fat content [ 43 , 49 , 52 ]. An absolute reduction in liver fat content has been reported in patients with NAFLD treated with empagliflozin in the E-LIFT Trial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the effects of various SGLT2 inhibitors on patients with T2DM and NAFLD [ 18 , 43 , 49 52 ]. They showed improvement in at least one liver enzyme level [ 31 , 43 , 49 , 50 , 52 ] and in hepatic fat content [ 43 , 49 , 52 ]. An absolute reduction in liver fat content has been reported in patients with NAFLD treated with empagliflozin in the E-LIFT Trial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean changes in AST and ALT concentrations showed no significant difference among the five groups of DPP-4 inhibitor users. Kusunoki et al previously reported that serum AST, ALT, and γ-GT concentrations were significantly decreased in patients with 6-month administration of combination therapy with a DPP-4 inhibitor and a sodium glucose co-transporter 2 (SGLT2) inhibitor [21]. Aoki et al previously reported that serum ALT and γ-GT concentrations were significantly decreased in patients with 16-week administration of combination therapy with alogliptin and pioglitazone compared with those with monotherapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…Four of these reported randomized, controlled, double-blind studies of liraglutide with a placebo (n = 3) or active (n = 1) comparator, and only one of these, the "Liraglutide Safety and Efficacy in Patients with Non-alcoholic Steatohepatitis (LEAN)" study, assessed histological endpoints using biopsy. Of note, of studies investigating liraglutide, only Insufficient data: 3 of 6 studies suggest modest benefit (7,36,38) and the other 3 suggest no benefit over comparator (30,37,59) Topiramate…”
Section: Glp-1 Agonistsmentioning
confidence: 99%
“…They were developed for the treatment of type 2 diabetes mellitus (T2D), but recent literature suggests pleiotropic effects including potential cardiovascular benefit and modest weight loss (79,80). Six studies have examined the effects of various SGLT2 inhibitors on patients with T2D and NAFLD (7,30,(36)(37)(38)59), but none to date have included histologic endpoints by biopsy. Five of the studies suggest improvement in at least one liver enzyme (7,30,(36)(37)(38)59), two showed improvement of hepatic fat content measured by liver-to-spleen ratio (30,59), and one, the "Effect of Empagliflozin on Liver Fat in Patients with Type 2 Diabetes and Non-alcoholic Fatty Liver Disease (E-LIFT)" trial, showed improvement of hepatic fat content measured by MRI-PDFF (36).…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%